2008
DOI: 10.1007/s11664-008-0458-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trace Amounts of Rare Earth Additions on Microstructure and Properties of Sn-Bi-Based Solder Alloy

Abstract: The effect of trace amounts of rare earth additions on the microstructure and properties were studied for the Sn-58Bi and Sn-58Bi-Ag solder alloys. At the same time, the intermetallic compounds (IMCs) in the solder alloys and intermetallic layer (IML) thickness at the solder/Cu substrate interface were investigated, both as-reflowed and after high-temperature aging. The results indicate that adding trace amounts of rare earth (RE) elements has little influence on the melting temperature and microhardness of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(60 citation statements)
references
References 21 publications
3
57
0
Order By: Relevance
“…In addition, the average approximate concentration of Sn, Cu, and Zn in the IMC layer adjacent to the Cu is also obtained which are 24, 56, and 20, respectively. These results which are consistent with the elemental-mapping analysis suggest that the IMC layer adjacent to the solder is a Cu 5 (Zn,Sn) 8 IMC layer while the IMC layer adjacent to the Cu substrate a Cu 6 (Sn,Zn) 5 IMC layer. The formation of Cu 6 (Sn,Zn) 5 IMC between Cu 5 (Zn,Sn) 8 IMC layer and the Cu substrate may be attributed to the penetration of Sn atoms through the Cu 5 (Zn,Sn) 8 IMC layer during the long solid-state reaction to form Cu 6 (Sn,Zn) 5 IMC.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…In addition, the average approximate concentration of Sn, Cu, and Zn in the IMC layer adjacent to the Cu is also obtained which are 24, 56, and 20, respectively. These results which are consistent with the elemental-mapping analysis suggest that the IMC layer adjacent to the solder is a Cu 5 (Zn,Sn) 8 IMC layer while the IMC layer adjacent to the Cu substrate a Cu 6 (Sn,Zn) 5 IMC layer. The formation of Cu 6 (Sn,Zn) 5 IMC between Cu 5 (Zn,Sn) 8 IMC layer and the Cu substrate may be attributed to the penetration of Sn atoms through the Cu 5 (Zn,Sn) 8 IMC layer during the long solid-state reaction to form Cu 6 (Sn,Zn) 5 IMC.…”
Section: Resultssupporting
confidence: 89%
“…The elemental analysis of the thermally aged solder joints revealed that a layer of Cu 6 (Sn,Zn) 5 IMC was also formed between Cu 5 (Zn,Sn) 8 and the Cu substrate after thermal aging for 1008 h.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sn-Pb solders [12,13]. In previous reports, Sn-58Bi solder alloys undergoing tensile tests have shown relatively high intensity values compared to other solder alloys; this indicates that brittleness is high, and fracturing has been observed during plastic deformation or elastic deformation [14,15]. The plastic deformation of Sn-58Bi solder can be improved by reducing the deformation rate.…”
Section: Introductionmentioning
confidence: 95%